The responsibility to protect remains a challenge: The plight of the Afghan interpreters - Ninna Nyberg Sørensen; Emma Katarina Andersen (Danish Institute for International Studies (DIIS), 2022)
In 2014, a DIIS policy study explored the past and future challenges of local interpreters working alongside Danish troops in military operations (Plambech and Danstrøm, 2014). The study focused on risks faced by local interpreters in different contexts; the human, economic and reputational costs involved; the outsourcing of recruitment to private contractors; and questions of accountability. The study provided both operational and policy recommendations. The aftermath of the evacuations that followed the withdrawal of US and NATO troops in August 2021, coupled with the expiration of the 'Danish agreement on the management of the situation for interpreters and other locally employed in Afghanistan' (Tolkeaftalen) by the end of 2022, provides an opportunity to access the role of local interpreters in military operations as well as the ethical and political dilemmas involved. The present working paper attempts to do so. It builds on a literature review of academic analyses, policy reports, a recent joint Danish government evaluation of the evacuation from Afghanistan, and interviews with representatives from Danish ministries and NGOs, the Danish Defence Command, relevant allies and other stakeholders. A shorter Danish language policy brief presents the main findings.
Keywords: 330; Local interpreters; Afghanistan; Denmark; USA; NATO; Danish NGOs; Danish Defense Command; translation needs; the Danish interpreting agreement; LEC; locally employed civilians; Taliban